Second-line rescue triple therapy with levofloxacin after failure of non-bismuth quadruple "sequential" or "concomitant" treatment to eradicate H. pylori infection. (June 2013) - Gisbert, Javier P.; Molina-Infante, Javier; Marin, Alicia C.; Vinagre, Gemma; Barrio, Jesus; McNicholl, Adrian Gerald
Abstract Background. Non-bismuth quadruple "sequential" and "concomitant" regimens, including a proton pump inhibitor (PPI), amoxicillin, clarithromycin and a nitroimidazole, are increasingly used as first-line treatments for Helicobacter pylori infection. Eradication with rescue regimens may be challenging after failure of key antibiotics such as clarithromycin and nitroimidazoles. Aim. To evaluate the efficacy and tolerability of a second-line levofloxacin-containing triple regimen (PPI–amoxicillin–levofloxacin) in the eradication of H. pylori after non-bismuth quadruple-containing treatment failure. Methods.Design: prospective multicenter study. Patients: in whom a non-bismuth quadruple regimen, administered either sequentially (PPI + amoxicillin for 5 days followed by PPI + clarithromycin + metronidazole for 5 more days) or concomitantly (PPI + amoxicillin + clarithromycin + metronidazole for 10 days) had previously failed. Intervention: levofloxacin (500 mg b.i.d.), amoxicillin (1 g b.i.d.) and PPI (standard dose b.i.d.) for 10 days. Outcome: eradication was confirmed with 13C-urea breath test 4–8 weeks after therapy. Compliance and tolerance: compliance was determined through questioning and recovery of empty medication envelopes. Incidence of adverse effects was evaluated by means of a questionnaire. Results. 100 consecutive patients were included (mean age 50 years, 62% females, 12% peptic ulcer and 88% dyspepsia): 37 after "sequential", and 63 after "concomitant" treatment failure. All patients took all medications correctly. Overall, per-protocol and intention-to-treat H. pylori eradication rates were 75.5% (95% CI 66–85%) and 74% (65–83%). Respective intention-to-treat cure rates for "sequential" and "concomitant" failure regimens were 74.4% and 71.4%, respectively. Adverse effects were reported in six (6%) patients; all of them were mild. Conclusion. Ten-day levofloxacin-containing triple therapy constitutes an encouraging second-line strategy in patients with previous non-bismuth quadruple "sequential" or "concomitant" treatment failure.